Survey and future directions of fault-tolerant distributed computing on board spacecraft. Issue 11 (1st December 2016) - Fayyaz, Muhammad; Vladimirova, Tanya
Abstract: Current and future space missions demand highly reliable on-board computing systems, which are capable of carrying out high-performance data processing. At present, no single computing scheme satisfies both, the highly reliable operation requirement and the high-performance computing requirement. The aim of this paper is to review existing systems and offer a new approach to addressing the problem. In the first part of the paper, a detailed survey of fault-tolerant distributed computing systems for space applications is presented. Fault types and assessment criteria for fault-tolerant systems are introduced. Redundancy schemes for distributed systems are analyzed. A review of the state-of-the-art on fault-tolerant distributed systems is presented and limitations of current approaches are discussed. In the second part of the paper, a new fault-tolerant distributed computing platform with wireless links among the computing nodes is proposed. Novel algorithms, enabling important aspects of the architecture, such as time slot priority adaptive fault-tolerant channel access and fault-tolerant distributed computing using task migration are introduced.